Aux Origines De La Question De L’emploi Salarie Et Du Chomage En Cote D’ivoire - Loba, Robert G. (European Scientific Journal, ESJ, 2016)
How did the notion of paid employment, so far unknown in the economic and social landscape of Côte d’Ivoire, impose itself upon the consciousness of the Ivorian populations? As a series of investigations made through documentary observations, following an approach both historical and dialectical, it appeared with the economic, social and cultural transformations introduced by the French colonisation. It is so well imbedded in the minds of the populations that it has become the main focus of most of the strategies of social promotion. Moreover, while before it everyone integrated himself harmoniously in economic fabric without trying to be employed by the other, its adoption as cardinal value has generated, with stupefying figures, unemployment which has become like an inescapable trap for the Ivorian youth.